Correlation between tumor necrosis factor-alpha and septic shock in children - Khrisanti Dinata; Ari L. Runtunuwu; Jose M. Mandei; Julius H. Lolombulan (Indonesian Pediatric Society, 2013)
Background The crucial role cytokines play in the pathophysiologyof sepsis is widely accepted. Infection stimulates the productionof cytokines in various cell types. Tumor necrosis factor-alpha(TNF-a) is one of the most extensively investigated cytokines inexperimental and clinical sepsis. Tumor necrosis factor-alpha hasbeen shown to mediate lethality in experimental sepsis.Objective To evaluate for a possible correlation between TNF-alevel and septic shock in children.Methods This cross-sectional study was conducted in Manadofrom June to September 2011. A total of 40 patients with arecent diagnosis of sepsis or septic shock were included. Plasmaspecimens were collected from subjects for measurement ofTNF-a concentration. Logistic regression analysis was used toassess the correlation between TNF-a level and sepsis, as well asthe probability of shock in children with sepsis, with P<0.05 asstatistically significant.Results There was a strong positive correlation betweenTNF-a level and the probability of shock in children with sepsis(regression coefficient = 0. 78, P = 0.002).Conclusions There is a strong positive correlation betweenTNF-a level with the probability of shock in children with sepsis.Higher plasma level ofTNF-a is associated with higher probabilityof septic shock.